Investigating the Effect of Hyoscine and Dexamethasone on Cervical Preparation in Primigravid Women with Term Pregnancy: A Double-blind Randomized Clinical Trial - Sheida Shabanian; Azar Danesh; Saba Najafi (Wolters Kluwer Medknow Publications, 2024)
Objective: Pregnancy outcomes are an important factor in women's quality of life, and negative experiences have adverse effects on the overall health of the mother and the family. This study was designed and implemented to compare the effects of two drugs, hyoscine and dexamethasone, on cervical ripening and effacement during childbirth. Methods: This study was a double-blind randomized clinical trial of 150 patients divided into three groups. The researchers, in the early stage (latent) of labor, gave 8 mg of dexamethasone intravenously to the first group, 20 mg of hyoscine butyl bromide to the second group, and 8 mg of dexamethasone along with 20 mg of hyoscine butyl bromide to the third group. Findings: Among the quantitative variables studied (length of labor induction, duration of active stage, first stage and second stage of labor, placental expulsion time, 5- and 10-min Apgar and Bishop score), active stage duration (P = 0.000) and 5-min Apgar (P = 0.042) had statistical differences among the three groups. In addition, the type of delivery (P = 0.003) and the percentage of fetal distress (P = 0.001) in the studied groups had a statistically significant difference, and also, in the third group, the cesarean rate was less than the other two groups. Conclusion: Simultaneous injection of hyoscine and dexamethasone in primiparous women can reduce the duration of the active stage of labor without obstetric complications, so its use in the latent stage is suggested.